2013
DOI: 10.1021/es403055e
|View full text |Cite
|
Sign up to set email alerts
|

Nationally Representative Levels of Selected Volatile Organic Compounds in Canadian Residential Indoor Air: Population-Based Survey

Abstract: A comprehensive, population-based national indoor air survey was conducted in 2009-2011 in Canada. A total of 84 volatile organic carbons (VOCs) from 3218 houses, 546 apartments, and 93 other dwelling types were measured using passive sampling followed by thermal desorption GC/MS. A total of 12 VOCs were measured in both this study and the 1992 Canadian national study. Arithmetic means of VOCs in this study were 2-5 times lower than those in the 1992 study with the exception of a higher styrene level (1.13 μg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 37 publications
5
47
1
1
Order By: Relevance
“…There are very few studies with which to compare our predictions of C 6 -C 10 aldehydes indoors and they are perhaps not directly comparable. However, our results are in reasonable agreement with a study that reports measured values in ~4000 Canadian households, 58 though tend to be on the higher end of the measured ranges (75th-99th percentile) except for hexanal which is closer to the geometric mean. Likewise, both Reiss et al 64…”
Section: Production From Indoor Materialssupporting
confidence: 92%
See 1 more Smart Citation
“…There are very few studies with which to compare our predictions of C 6 -C 10 aldehydes indoors and they are perhaps not directly comparable. However, our results are in reasonable agreement with a study that reports measured values in ~4000 Canadian households, 58 though tend to be on the higher end of the measured ranges (75th-99th percentile) except for hexanal which is closer to the geometric mean. Likewise, both Reiss et al 64…”
Section: Production From Indoor Materialssupporting
confidence: 92%
“…report mean mixing ratios of closer to 1 ppb. For nonanal, our values are relatively high compared to the measurements of Zhu et al., who report a 99th percentile value of ~2.5 ppb. However, the painted walls make a significant contribution to our predicted concentrations and the yield values used are based on relatively few measurements.…”
Section: Resultscontrasting
confidence: 58%
“…Mixing ratios of acetic acid and formic acid were measured in residences in New Jersey and in the greater Boston area at levels comparable to the current study and also more than an order of magnitude higher than outdoors . An indoor air survey of ~3800 homes in Canada showed that furfural was detected in 98% of homes (acetic acid was not a target compound in that study) . Another study in Finland showed that furfural was detected in 21 out of 26 houses .…”
Section: Resultssupporting
confidence: 70%
“…One major concern regarding residential indoor air quality is elevated concentrations of volatile organic compounds (VOCs) . Indoor VOCs encompass a broad range of chemical species, including saturated and unsaturated hydrocarbons, carbonyls, alcohols, organic acids, ethers, esters, furanoids, amines, siloxanes, sulfides, etc . Some VOCs are known to pose health hazards, some may be important for indoor chemistry, and few have been well characterized .…”
Section: Introductionmentioning
confidence: 99%
“…Median concentrations of aldehydes were slightly higher, whereas there were lower for other VOCs, except for decane and undecane. Regarding a recent Canadian study (Zhu et al, 2013), median concentrations were comparable for benzene, toluene, ethylbenzene, xylenes, and limonene. However, we found a slightly higher concentration of a-pinene.…”
Section: Voc Concentrationsmentioning
confidence: 82%